Knowledge of Blood Transfusion among Nurses at Hospital Pulau Pinang: Nursing Responsibilities and Patient Management Related to Transfusion Reactions - Lim, Elaine Siew Lee; Abdul Rahim, Nur Arzuar; Tuan Din, Sharifah Azdiana (Penerbit Universiti Sains Malaysia, 2016)
Introduction: Nurses are generally trained on the procedures of blood transfusion during their years of service. However, the level of knowledge varies among individuals and healthcare centres. Thus, this study addresses a knowledge gap regarding nurses’ knowledge and transfusion safety in the local clinical setting. Objectives: This study aimed to determine nurses’ level of knowledge of various phases of blood transfusion and associate this knowledge with their socio-professional details. Methods: This was a cross-sectional, quantitative study. The target population was in-patient ward nurses at Hospital Pulau Pinang. The systematic random sampling method was used to select 185 nurses to participate in this study. Data were collected using a validated research questionnaire that consisted of 31 items (9 items related to socio-professional factors and 22 knowledge items). Data were analysed using descriptive and inferential analyses. Results: The overall knowledge score was moderate (mean = 70.44%, SD = 11.35). None of the nurses was able to answer all of the knowledge questions correctly. Of the participants, 72.29%, 71.75%, and 67.14% exhibited knowledge of blood bag collection and patient preparation; pre-transfusion nursing activities; and during and post-transfusion nursing responsibilities and management of transfusion reactions, respectively. Factors such as age, years of service, department, and availability of the transfusion policy in the ward significantly affected the mean knowledge scores. Conclusion: Nurses’ knowledge of blood transfusion at Hospital Pulau Pinang was moderate. More training and courses should be provided to improve their knowledge.